KELUARGA HARMONIS UNTUK PERKEMBANGAN POTENSI ANAK YANG LEBIH BAIK - Ahmad Masrur Firosad (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2015)
The family is the initial education phase traversed by a child, where the child would spend more time with family. Education in the family becomes very important for the growth and development of each child's potential. If children live in a harmonious family environment it will be a positive influence on children's growth and development potential. However, if a child is raised in a broken home family environment, it will negatively affect the child's growth and development potential.